Structural performance of recycled aggregate in CSP slab subjected to flexure load - Mohamad, Noridah; Abdul Samad, Abdul Aziz; Goh, Wan Inn; Mendis, Priyan; Hamza, Khalifa (Elsevier Ltd., 2016)
This paper discusses the mechanical properties of recycled aggregate concrete (RAC) and its performance in concrete sandwich precast (CSP) slab subjected to flexure load. Various percentage of recycle aggregate (RA) was used in the concrete mixture as a replacement to natural aggregate; namely 25%, 50%, 75% and 100%. The structural behavior of the CSP slab was investigated experimentally under flexure load and analyzed in the context of its ultimate load capacity, crack pattern, load-deflection profile and load-slip profile. Analysis from the results showed that the percentage of RA used has a small effect on the mechanical properties of RAC but quite significant effect on the structural behavior of CSP slab under flexure. It was found that the strength of the panels with RAC decreased with the increase of RA in the concrete. The percentage of reduction in the ultimate load of slab panels with RA was about 15% for every 25% percentage increase of RA. The first crack occurred at about 48–67% of the failure load and panels failed with excessive cracks in the tension zone of the bottom wythe. All tested panels proved to be very ductile with large deformation prior to failure and behaved in a partially composite manner.